Pengamanan Pesan Teks Terenkripsi Algoritma AES yang Disembunyikan kedalam Citra Menggunakan Algoritma Gifhsuffle - Octariza, Hary (Bulletin of Data Science, 2024)
The advancement of information systems in the field of computer science and telecommunications is growing and advancing rapidly. Computer technology is needed for office or personal work to be faster, data exchange is easier to do. Data can be in the form of messages in the form of text, images, audio or video. Data that is private and confidential cannot be known by the public or published. The combination of cryptographic techniques and steganographic techniques can increase the security of text messages so as to minimise the occurrence of text message damage that can be done by irresponsible parties and harm the owner of the text message. The AES algorithm is an algorithm that can perform cryptographic techniques, while the Gifhsuffle algorithm is an algorithm that can perform steganographic techniques. This research uses the AES algorithm for the encryption and decryption process and uses the Gifhsuffle algorithm for the encoding and decoding process. A file containing a message will be encrypted using the AES algorithm to produce a ciphertext followed by hiding it in a GIF-formatted image file using the Gifhsuffle algorithm encoding process to produce a Stego Image. This process can increase the security of the message and make it difficult for irresponsible parties to find the message.